(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes contemporary methodological approaches to preparing future primary school teachers for developing reading literacy among students. Based on an examination of international experience and scientific-pedagogical literature, the study explores ways to improve teacher-training programs, effective pedagogical strategies and methods, as well as existing shortcomings in teacher education and approaches to addressing them. The article discusses instructional methods for teaching key components of reading literacy such as phonemic awareness, phonics, fluency, vocabulary development, comprehension, and assessment. It further recommends differentiated instruction, cognitive strategies, and evidence-based teaching approaches. The theoretical and practical foundations of global assessments (PIRLS, PISA), national curricula, competency-based education, digital and innovative methods (Learning Analytics, gamification, STEAM), and integrative technologies are examined in detail. The paper also provides scientifically grounded recommendations for enhancing teachers’ methodological readiness, lesson-design competencies, and diagnostic and assessment mechanisms. The research findings contribute to increasing the preparedness of future teachers to effectively develop students’ reading literacy.